PENINGKATAN KEMAMPUAN BELAJAR PERDAGANGAN INTERNASIONAL DENGAN TEKA-TEKI EKONOMI PADA SISWA KELAS XI-IPS - Ani, Risa Ari (Dinamika Pendidikan, 2014)
The materials of international trade are full of economic theories and terms which make students difficult to understand the materials, so it needs a medium to facilitate students in learning. The purpose of this study was to determine the use of Economics Puzzle learning media to improve studentsâ understanding of open economy material. It was a Class Action Research with 2 cycles done in SMA N 1 Mranggen at the 2nd semester of the academic year 2013/2014. The subjects of the study were 31 students of class XI IPS 2. The results showed that the average of studentsâ learning outcomes was 73 on the 1st cycle and increased up to 76 on the 2nd cycle. The classical achievement also increased from 87% on the 1st cycle up to 94% on the 2nd cycle.Â